(untitled) (Research, Society and Development, 2021)
Low back pain is a condition that can reach up to 65% of people annually and up to 84% of people at some point in life, being the second most prevalent health condition in Brazil (13.5%) among chronic pathologies. The aim of this study was to evaluate the effect of Pelvic Suspension on pain, spine mobility and functional capacity of individuals with low back pain. The study participants were 10 adult patients, of both sexes, diagnosed with low back pain. The participants were submitted to initial and final evaluation of trunk mobility, by the measurement of flexion range of motion, extension and lateral inclination, pain intensity by the visual analog scale and presence of functional disability by the Oswestry Disability Index. The intervention consisted of 10 sessions of Pelvic Suspension. Pain intensity showed an initial mean of 4 (moderate pain) and final mean of 0.8 (no pain). The evaluation of trunk mobility showed increased flexion of the spine in 6 individuals, 4 showed no modification. Increased spine extension in 6 individuals, 2 had reduction and 2 showed no alteration. Functional disability presented an initial mean index of 40% (moderate disability), while in the final evaluation the mean index was 18.87% (minimum disability). The study showed reduced pain perception, increased spine mobility and reduced functional disability of patients with low back pain who used pelvic suspension therapy.